Correspondencia entre Roberto H. Todd, Luis Raúl Estéves y Margarita y Rosa Emanuelli. - Todd, Roberto H.; Esteves, Luis Raul; Emanuelli, Margarita y Rosa (My University, 1940)
Recordando al General Miles.
Keywords: Miles, Nelson A.